Transient CREB-mediated transcription is key in direct neuronal reprogramming. Issue 1 (1st January 2017) - Gascón, Sergio; Ortega, Felipe; Götz, Magdalena
ABSTRACT: Combinations of neuronal determinants and/or small-molecules such as Forskolin (Fk) can be used to convert different cell types into neurons. As Fk is known to activate cAMP-dependent pathways including CREB-activity, we aimed here to determine the role of CREB in reprogramming – including its temporal profile. We show that transient expression of the dominant-positive CREB-VP16 followed by its inactivation mediated by the dominant-negative ICER improves neuronal conversion of astrocytes mediated by the neurogenic determinant Ascl1. Contrarily, persistent over-activation by CREB-VP16 or persistent inhibition by ICER interferes with neuronal reprogramming, with the latter enhancing cell death. Taken together our work shows transient CREB activation as a key effector in neuronal reprogramming.